Islam and Pluralism in the Qur'anic Perspective:Thematic Interpretive Studies: Islam dan Pluralisme dalam Perspektif Al-Qur'an: Kajian Tafsir Tematik - Dani Ramdani; Dewi Lutfiyatul Hilwa; Fawwaz Fauzan Muzani (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Contemporary Issues is a study that discusses various issues in the modern era. The main core of this study is Islam and pluralism. The discussion covers contemporary issues that are analyzed through a thematic interpretive lens. The purpose of this study is to examine contemporary issues related to Islam and pluralism through the interpretation of the Quran. The discussion includes the meaning of pluralism itself and the interpretations of classical and contemporary commentators. The research method is the search for meaning and references. The findings of the study on Islam and pluralism show that pluralism means diversity, this has been repeatedly explained in the Quran, such as Surah Al-Baqarah verse 62 and Surah Ar-Rum verse 22. This research is useful in advancing teaching activities and providing learning materials to those who need them.